Meanings of ME: Interpersonal and Social Dimensions of Chronic Fatigue
XI, 231 p.
Keywords: Chronic Fatigue Syndrome (CFS or ME) is a problematic diagnosis which can be interpreted in conflicting ways by doctors, patients and others. Meanings of ME signals a paradigm shift in thinking about the illness by providing fresh perspectives from doctors, clinicians and those who have personal knowledge of CFS/ME.